Oral health promotion for schoolchildren - evaluation of a pragmatic approach with emphasis on improving brushing skills - Slouk Liat; Vered Yuval; Livny Alon; Sgan-Cohen Harold D (BMC, 2008)
Abstract Background Preventive dentistry has traditionally emphasized improvement of oral hygiene. School-based programs, often delivered by dental hygienists or other health educators, are usually limited to dental knowledge provision. The present study focused on promotion of health behavior. The objectives were to evaluate the effect of a pragmatic educational program on tooth brushing skills of young schoolchildren. Methods The population consisted of 196 first grade children in Jerusalem. One dentist interviewed the children and evaluated base-line brushing skills, applying simple visual index, based on dividing the dentition to eight different segments. a trained hygienist then educated the children, emphasizing brushing skills. A simple "scrubbing" brushing method was taught for all dental surfaces. Four months later a second examination was conducted, applying same evaluation methods. Results At base-line 92% of the children had brushed the labial surfaces of front teeth, but only 8% brushed the inner surfaces of posterior teeth. Only 32% brushed occlusal surfaces. These levels significantly increased after four months: 98% now brushed the labial surfaces; 43% brushed inner surfaces of posterior teeth, 87% brushed occlusal surfaces (p < 0.001). The average number of dental "areas" brushed had increased (among the eight areas recorded) from 2.8 to 5.7 (p < 0.0001). Conclusion This method of behavioural instruction emphasized improvement of personal manual skills specifically for those areas of the dentition which demand most efforts in oral hygiene promotion. These results are of practical help in improving future health education programs by the health promotion team.